Avaliação dos efeitos antitumorais do complexo de rutênio [Ru(GA)(dppe)2]PF6 em células não-tumorais e tumorais de mama cultivadas in vitro - Naves, Marina Araújo (2017)
Cancers have become an increasingly relevant problem of public health in the last decades. Within neoplastic diseases, breast cancer is one of the most incidental in female population and related to a high mortality rate. Within types of breast cancer, triple-negative is the most aggressive one and prone to form metastasis to lung and brain. Because they do not express hormone receptors, triple-negative tumors do not have an auxiliary target therapy, thus, treatment is hampered and chemotherapy is the only option of treatment remaining for metastatic cases of this tumor type. However, chemotherapy drugs currently used, in some cases are not selective to tumor cells, acting only on the proportion of cells exposed to treatment or cells that are at certain stages of the cell cycle. Thus, non-tumor cells are affected and some neoplastic cells remain intact, characterizing tumor recurrences and resistance to treatment. Rosenberg and colleagues, in 1964, were responsible for the discovery of cisplatin, a metal and antiproliferative compound still widely used in therapies against various types of tumors, but despite its effectiveness, it has several side effects. Therefore, the search for more selective antitumor drugs for neoplastic cells and with fewer adverse effects is critical to advances in the treatment of cancer. With the limitations of cisplatin, new researches have been developed with ruthenium complexes. Ruthenium has properties that may justify its antitumor potential and selectivity for tumor cells; within them, the ability to imitate iron binding to many biomolecules, including transferrin and albumin. Previous studies have suggested the antitumor effects of ruthenium both in vitro and in vivo. Therefore, the aim of this study was to evaluate the chemosensitizing ability of the ruthenium complex [Ru(GA)(dppe)2]PF6, which we called Ru(GA), as well as its antitumor activity on triple-negative breast cancer cells (TNBC). In addition, differences between the in vitro behavior of cells treated with the compound and untreated cells were verified, as well as differences between the activity on tumor and non-tumor cells used in this study. The results demonstrated that the complex Ru(GA) was more efficient in inhibiting the proliferation of triple negative breast cancer cells MDA-MB-231, compared with the non-tumor cell line MCF-10A, which was more resistant to the complex. Furthermore, the compound was able to reduce the number and size of colonies, to modify the cytoskeleton and act inhibiting the migration ability of tumor cells. The complex also induced apoptosis by increasing the expression of pro-apoptotic genes such as Bax, Caspase-9, Caspase-3 and decreasing anti-apoptotic genes Bcl-2 in TNBC cells. Moreover, Ru(GA) was able to increase the expression of apoptotic proteins and sub-G1 phase distribution on tumor cells. Interaction assays with Ru(GA) and transferrin showed that this protein has a strong participation in the contact between ruthenium complexes and tumor cells, increasing their effectiveness. These results show that the complex Ru(GA) has antitumor potential against breast tumor cells and it might be a good alternative drug for the treatment of cancer.